Analisis Kemampuan Membaca Pemahaman Siswa Kelas VI SDN 2 Girijaya dalam Memahami Teks Narasi - Dini Windarini; Asep Nurjamin (Yayasan Al-Afif, 2026)
This study aims to analyze the reading comprehension ability of sixth-grade students at SDN 2 Girijaya in understanding narrative texts based on Barrett’s Taxonomy. The research employed a descriptive quantitative approach involving 40 students as research participants. Data were collected through a reading comprehension test covering five levels: literal, reorganization, inferential, evaluative, and appreciative. The research instrument was developed in the form of essay questions based on the indicators of Barrett’s Taxonomy. The data were analyzed using descriptive statistical techniques to obtain the mean scores, percentages, and categories of students’ reading ability. The results show that students’ reading comprehension ability is in the good category, with an average score of 77.82. Students demonstrated adequate mastery of literal and reorganization aspects, while variations were found in inferential, evaluative, and appreciative aspects. Some students experienced difficulties in drawing conclusions, providing evaluations, and relating the content of the text to personal experiences. The findings indicate that reading instruction needs to be directed toward strengthening higher-order thinking skills through systematic and continuous learning strategies. The application of Barrett’s Taxonomy proved effective in mapping students’ reading comprehension abilities in a structured manner. This study is expected to serve as a reference for developing reading instruction in elementary schools. Keywords: reading comprehension, narrative text, Barrett’s Taxonomy, elementary school, reading ability